Management of Inheritance Assets Between Heirs (Case Study of Gampong Kayukul, Pegasing District, Central Aceh Regency): Pengelolaan Harta Warisan Antar Ahli Waris (Studi Kasus Gampong Kayukul Kecamatan Pegasing Kabupaten Aceh Tengah) - Hidayah, Shofia (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2021)
Inheritance is property left by the testator after death. Inheritance in Islam is regulated in inheritance law, which is the law governing the transfer of property from a deceased person to a living family. In Islam, after a person dies, the inheritance he leaves must be immediately distributed to his heirs. But in fact, along with the development of the times, many things have changed, such as the inheritance distribution system in Islam, where people take the initiative to first manage their inheritance. Based on this, the authors are interested in researching this problem with the formulation of the problem, namely how are the practices, impacts, and views of Islamic law regarding the management of inheritance between heirs that occurred in Kayukul Village, Pegasing District, Central Aceh Regency. This research is a qualitative research with field research, the approach used is a normative-sociological approach. The legal materials used are primary legal materials and secondary legal materials sourced from books, scientific works and research results in the field. Data collection techniques used are observation and interviews. The result of this research is that in Gampong Kayukul the management of inheritance between heirs is carried out by working on and managing the estate in the form of a garden together which then the results are used for daily needs. Then the management of this inheritance has a positive impact on the individual or each heir, while the negative impact comes from external. Regarding the view of Islamic law on the management of inheritance between heirs, this is something that is permissible as long as there is a prior agreement between the heirs and there is the pleasure or willingness of all heirs.